A retrospective study of intramedullary tibia nailing system intended for tibia fracture - Sharma, Pallavi; Jain, Arpit; Luthra, Gaurav (International Journal of Research in Orthopaedics, 2022)
Background: The aim of the study was to investigate the performance of the intramedullary tibia nail in the treatment of tibia fractures, mostly shaft fractures. The objective of this study was to assess the post-operative complication due to the treatment involving tibia nails. Methods: This was a retrospective study to study the results obtained after tibia nail surgery. A total of 32 patients were selected based on inclusion and exclusion criteria (25 males and 7 females; average age- 37 years). The fracture was classified according to AO classification, the nailing device is intended for 41-A1/A2, 42 and 43-A1/A2/A3 types of fractures. The patients with at least three visits within 180 days were selected for data collection. Results: The clinical outcomes include pain scale assessment from the baseline/enrolment to the last follow up which shows no pain (93.7%) and mild pain (6.7%) after 180 days. No implant-related problems like implant loosening. Conclusions: For the treatment of tibia shaft fracture which can either be closed or open, intramedullary tibia nailing devices like KN-2T and KN-5T have been concluded to be the good approach.